A foreign policy oriented toward personal interests: An analysis of Bolsonaro's approach to multilateralism. (18th October 2022) - Soares de Lima, Maria Regina; Albuquerque, Marianna
Abstract: Historically, Brazilian diplomacy has centered its foreign policy strategy on multilateral institutions. Multilateralism has not only been an instrument to share the political costs of international decisions but also a defensive mechanism, due to Brazil's modest military capability. In this article, we consider that Bolsonaro's multilateral foreign policy represents the rupture of narrative. Departing from the premise that foreign policy is a public policy, hence subjected to domestic constituencies, Bolsonaro's conservative project is constructed in the intersection between domestic politics and the international system. First, we introduce our main hypothesis, that he employs an ideology of anticommunism, antiglobalism, and negationism to assure the loyalty of specific constituencies despite potential disruptions to collective interests and national long‐term strategies. Next, we connect the internal to the external by comparing Bolsonaro's approval in public opinion polls and his proposition or support of domestic laws to Brazil's stance in multilateral forums. To verify the validity of our argument, we aim to identify patterns of external behavior that correspond to the president's political ideas and guidelines and to concrete interests of domestic constituencies. Resumen: Históricamente, la diplomacia brasileña ha centrado su estrategia de política exterior en las instituciones multilaterales. El multilateralismo no solo ha sido un instrumento para compartir los costos políticos de las decisiones internacionales, sino también un mecanismo defensivo, debido a la capacidad modesta militar de Brasil. En este artículo, consideramos que la política exterior multilateral de Bolsonaro representa una ruptura de narrativa. Partiendo de la premisa de que la política exterior es una política pública, por lo tanto, sujeta a los electorados domésticos, el proyecto conservador de Bolsonaro se construye en la intersección entre la política doméstica y el sistema internacional. Primero, presentamos nuestra hipótesis principal—Bolsonaro emplea una ideología anticomunista, de antiglobalismo y negacionismo para asegurar la lealtad de grupos específicos a pesar de las posibles perturbaciones de los intereses colectivos y las estrategias nacionales a largo plazo. Posteriormente, conectamos lo interno con lo externo comparando la aprobación de Bolsonaro en las encuestas de opinión pública y su propuesta o apoyo a las leyes internas con la postura de Brasil en los foros multilaterales. Para verificar la validez de nuestro argumento, nuestro objetivo fue identificar patrones de comportamiento externo que correspondan a las ideas y directrices políticas del presidente y a los intereses concretos de los electorados nacionales. 摘要: 从历史上看，巴西外交一直将其外交政策战略集中在多边制度上。鉴于巴西的军事能力有限，多边主义不仅是一种分担国际决策政治成本的工具，也是一种防御机制。本文中，我们认为博索纳罗的多边外交政策代表了叙事的破裂。本文以外交政策是公共政策（因此受制于国内选民）为出发点，在国内政治与国际体系的交叉处建构博索纳罗的保守主义计划。第一，我们介绍了主要假设，即博索纳罗采用反共产主义、反全球主义和否定主义的意识形态来确保特定选民的忠诚，尽管这可能会破坏集体利益和国家长期战略。第二，我们将内部与外部联系起来，比较了博索纳罗在民意调查中的支持率以及他在多边论坛中对关于巴西立场的国内法律的主张或支持。为了验证论点的有效性，我们旨在识别一系列外部行为模式，后者对应了总统的政治思想和指导方针以及国内选民的具体利益。